2018
DOI: 10.1039/c8dt02848f
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene containing amino-ether macrocycle based Cu(ii) templated [2]pseudorotaxanes and OFF/ON fluorescence switching via axle substitution

Abstract: A new naphthalene containing macrocycle, NaphMC, and a new fluorophoric bidentate linear axle derivative of 5,5'-dimethyl-2,2'-bipyridine (L3) along with two other ligands 1,10-phenanthroline (L1) and 5,5'-dimethyl-2,2'-bipyridine (L2) are explored towards the synthesis of Cu(ii) templated [2]pseudorotaxanes. All ternary complexes are well characterized by ESI-MS, UV/Vis, EPR spectroscopy, elemental analysis and emission spectroscopic studies. Single crystal X-ray diffraction studies confirm the geometry aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Since the invention of mechanically interlocked molecules (MIMs), exploration of their inherent properties has broadened the areas of molecular sensing, 1 switching, 2 shuttling, 3 catalysis, 4 etc. Consequently, numerous templating strategies, like hydrogen bonding, 5 π–π stacking, 6 anion templation, 7 metal–ligand coordination 8 and other assembly strategies, 9 have been established for the synthesis of functional interlocked architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Since the invention of mechanically interlocked molecules (MIMs), exploration of their inherent properties has broadened the areas of molecular sensing, 1 switching, 2 shuttling, 3 catalysis, 4 etc. Consequently, numerous templating strategies, like hydrogen bonding, 5 π–π stacking, 6 anion templation, 7 metal–ligand coordination 8 and other assembly strategies, 9 have been established for the synthesis of functional interlocked architectures.…”
Section: Introductionmentioning
confidence: 99%
“…This study assists in finding the most favourable combination of macrocycle, selective metal and chelating ligand to form stable [2]pseudorotaxane. 14,15 Furthermore, the crystal structure analysis confirmed that during ternary pseudorotaxane formation, Ni II and Cu II prefer the corresponding hexa ( P1 ) and penta ( P2 , P3 ) orthogonal coordinations, respectively. Such coordination around the metal is satisfied by the tris amine moiety of the wheel, bidentate axle and solvent molecule wherever applicable (Fig.…”
Section: Mechanically Interlocked Architectures With Heteroditopic Wh...mentioning
confidence: 76%
“…13 To explore metal templation based multi-functional MIMs further, Ghosh and co-workers recently developed several new combinations of heteroditopic macrocycles, i.e. amido-triamine ( W2 ), 14 oxy-ether-triamine ( W3 , W4 ) 15 and oxy ether-Phen-ester ( W5 ) 16 wheels. Using anion templation, Beer and co-workers developed different heteroditopic macrocycles depending on isophthalamide/calix[4]diquinone/triazole/oxy-ether ( W6–W7 , W9 ) motifs.…”
Section: Macrocyclic Wheels With Heteroditopicitymentioning
confidence: 99%
“…[11][12][13][14][15] In recent times, polyaromatic hydrocarbons/heterocycles (PAHs) were used in place of one or more pyrrole rings of porphyrinoids to generate a new type of polyaromatic embedded porphyrinoids with interesting electronic and coordination properties. [16,17] A perusal of literature revealed that the polyaromatic hydrocarbons/heterocycles such as biphenyl, [18] naphthalene, [19] phenanthrene, [20] fluorene [21,22] bipyridine, [23] phenanthroline, [24] dibenzofuran, [25] dibenzothiophene, [26] and phenothiazine [27] are few such polyaromatic hydrocarbons/heterocycles which have been introduced in place of one or more pyrrole rings of porphyrinoid framework and generated a wide range of very novel PAH embedded porphyrinoids. We used few of these PAH units such as dibenzofuran, dibenzothiophene, benzofuran, benzothiophene, fluorene and phenothiazine and synthesized very novel PAH embedded porphyrinoids which showed unique and interesting electronic and coordination properties.…”
Section: Introductionmentioning
confidence: 99%